MARRIAGE CUSTOMS OF THE MUARASIPONGI BORDER COMMUNITY: AN ISLAMIC LEGAL SOCIOLOGY APPROACH - Aminuddin, Aminuddin (Program Pascasarjana UIN Sumatera Utara Medan, 2024)
This research is about the cultural customs of marriage in the border communities of Muarasipongi, North Sumatra and West Sumatra provinces from the perspective of the sociology of Islamic law, the order of customary law in Indonesia which is the main problem in marriage which is captured from the perspective of the sociology of Islamic law with cultural diversity that is aligned with the pattern of life in society and the difference in the form of customary marriage law due to the difference in kinship system or system descendants embraced by each customary law community in Indonesia. Law is essentially in a customary law society where a social system arises that is studied using sociological approaches to Islamic law, so a neutral picture is obtained. Identification of problems that may occur in the process of meeting customary and cultural law with Islamic law is captured from the sociological side of Islamic law, without prejudice, the most important thing is that the law truly fulfills the sense of justice of the community and its citizens. The type of research used is normative juridical, which is to provide the most complete overview of cultural customary law norms from the perspective of legal sociology. The method applied is empirical juridical, because from a juridical point of view, this study examines customary law regulations which are used as a basis for resolving legal problems based on custom. The results of the study show that in the Muarasipongi border community, there are various variations of marriage cultural customs chosen by both parties by agreement. For example, the Orang ulu Muarasipogi use the sumondo marriage system, while the Mandailing people use the manjujur marriage system. Many factors affect the process of choosing this marriage custom. Because the difference in the cultural customs of this marriage is first decided between the families of both parties and the local traditional elders, so that it does not cause conflict